2015
DOI: 10.1111/omi.12142
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual immunization with the phosphate‐binding‐protein (PstS) reduces oral colonization by Streptococcus mutans

Abstract: Bacterial ATP-binding cassette (ABC) transporters play a crucial role in the physiology and pathogenicity of different bacterial species. Components of ABC transporters have also been tested as target antigens for the development of vaccines against different bacterial species, such as those belonging to the Streptococcus genus. Streptococcus mutans is the etiological agent of dental caries, and previous studies have demonstrated that deletion of the gene encoding PstS, the substrate-binding component of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
(44 reference statements)
0
13
0
3
Order By: Relevance
“…Recently, a vaccine trial in mice using LT derivative (detoxified) as an adjuvant with the subunit of Pi 39‐512 and PstS protein has also been shown to elicit antigen‐specific antibody production and a reduction in the adherence of Strep. mutans (Ferreira et al ; Batista et al ).…”
Section: Lessons Learned and Where Are We Today?mentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, a vaccine trial in mice using LT derivative (detoxified) as an adjuvant with the subunit of Pi 39‐512 and PstS protein has also been shown to elicit antigen‐specific antibody production and a reduction in the adherence of Strep. mutans (Ferreira et al ; Batista et al ).…”
Section: Lessons Learned and Where Are We Today?mentioning
confidence: 99%
“…First, to search for new target virulence genes or antigenic proteins, develop vaccines, use the best historically proved adjuvant and administration technique and enhance further using nanotechnology. For example, Ferreira et al () studied a completely new protein, PstS, which showed promising results. Second, existing best‐proved animal trial vaccines can be improved to the required level.…”
Section: Future Directionmentioning
confidence: 99%
See 2 more Smart Citations
“…Um trabalho publicado em 2016 por nosso grupo de pesquisa, demostrou que a imunização sublingual de camundongos BALB/c utilizando como antígeno modelo uma proteína captadora de fosfato do sistema ABC de S. mutans, a proteína PstS em combinação ou não com a enterotoxina mutante LTK4R, foi capaz de estimular a produção de anticorpos sistêmicos e também ativar células secretoras de IgA no baço e linfonodos cervicais. Além disso, foi observado que os anticorpos gerados após o regime vacinal adotado foram eficientes em interferir na capacidade de colonização oral por S. mutans(59).…”
unclassified